Analisis Strategi Pemasaran Negatif Terhadap Kepercayaan Konsumen pada Perusahaan Skincare: Studi Kasus SS Skin - Ikmila Khoerunnisa; Halimah Zahrah; Novi Ramadani (Teewan Journal Solutions, 2025)
This anality aims to analyze the impact of negative marketing strategies on consumer trust in local skincare companies through a case study of SS Skin. A descriptive qualitative approach was employed using netnographic observation, and digital document analysis. The results show that promotional content containing hyperbolic claims such as “bright skin in 3 days without irritation” creates unrealistic expectation, leading to disappointment when actual outcomes differ. Sentiment analysis of netizen comments revealed dominant negative responses including distrust toward the brand and regulatory institutions. Compared to other cases like Scarlett Whitening and Kylie Skin, SS Skin’s failure in crisis communication worsened public perception. This study concludes that negative marketing strategies can cause systemic effects on the reputation of local brands and the overall trust in the skincare industry. Therefore, ethical, transparent, and evidence-based marketing communication is essential for building sustainable customer loyalty.